Risk spillover among hedge funds: The role of redemptions and fund failures - Benjamin Klaus; Bronka Rzepkowski (European Central Bank (ECB), 2009)
This paper aims at analysing the mortality patterns of hedge funds over the period January 1994 to May 2008. In particular, we investigate the extent to which a spillover of risk among hedge funds through redemptions and failures of other funds has affected the probability of fund failure. We find that risk spill-over is significantly related to the failure probability of hedge funds, with the relation being more pronounced for redemptions than for failures of other funds. Hedge funds within the same investment style are adversely affected through both channels of risk spillover. In addition, we find that funds being diversified in assets and geographically have a significantly lower failure probability and are not affected by risk spillover via redemptions.
Keywords: G11; G20; G23; G33; 330; diversification; Hedge Funds; Risk Spillover; Survival Analysis; Hedgefonds; Statistische Bestandsanalyse; Risiko; Spillover-Effekt; Diversifikation